HRMS: IS THE ROLE CHANGING FROM BEING ADMINISTRATIVE TO STRATEGIC? - Mahajan, Goldy; Mehta, Prof. Versha (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
Human Resource Management System (HRMS) seems to matter for Human Resource Management (HRM) in the current digital economy. Many firms transform their HRM functions from the manual work processes to the computerized work processes. Information technology is expected to drive Human Resource (HR)’s transition from a focus on Human Resource Management (HRM) to Strategic Human Resource Management (SHRM). This strategic role not only adds a valuable dimension to the HR function, but also changes the competencies that define HR professional and practitioner success. Interestingly, an HRMS is utilized for administrative purposes rather than analytical purposes. The study focused on the implementation of HRMS in the J&K BankÂ and attempts to investigate whether Human Resource Management Systems have reached the strategic potential in HR department or not.